FIDIC force majeure clause from the viewpoint of Serbian law - Stojković Sara (Anali Pravnog Fakulteta u Beogradu)
The purpose of this paper is to present force majeure as stipulated in FIDIC forms, which are nowadays frequently in use when negotiating the conclusion of construction contracts concerning major projects. An important remark is that these forms have been greatly influenced by common law systems where operation of force majeure is dependent on the contractual definition and wording of the clause. On the other hand, the Serbian Law on Obligations contains its own understanding of force majeure-related concept, which might be amended in accordance with the principle of party autonomy. The paper further aims to elaborate on this interplay between these FIDIC forms and Serbian law. The conclusion is that the FIDIC force majeure clause represents an important contribution to the domestic regime, which does not expressly address scenarios with temporary impediments, which is necessary for successful completion of construction works.